Variations of musculocutaneous nerve – A cadaveric study - Anju George; Maheswary Thampi S; Aswathy VA; Geetha Jayachandran (Asian Journal of Medical Sciences, 2024)
Background: Musculocutaneous nerve (MCN) is a mixed nerve arising from the lateral cord of brachial plexus having root values C5, 6, and 7. It supplies the muscles of the flexor compartment of the arm namely; coracobrachialis, most part of brachialis and both heads of biceps brachii. It is cutaneous to the lower lateral part of forearm. Variations in the origin, course, branching pattern, termination, and connections of MCN are very common. Knowledge about these variations is important while evaluating unusual presentations of peripheral nerve injuries, during surgical procedures such as arthroscopy of shoulder joint, corrections of fracture humerus, brachial plexus block, and so on. Aims and Objectives: The study was conducted to find out any variations in the origin, course, branching pattern of the MCN. The secondary objective was to understand about the communication of the MCN with any other nerve. Materials and Methods: A descriptive study was conducted in 60 upper limb specimens dissected from 10% formalin embalmed 30 cadavers (adult) in the Department of Anatomy, Government Medical College, Kottayam. All limbs were carefully dissected and studied about the origin, course, termination, and variations of MCN. Results: Out of 60 specimens studied, in 46 specimens MCN Originate from lateral cord, eight from medial cord, and in six from the lateral root of the median nerve (MN). In 52 specimens, MCN supplies coracobrachialis but only in 34 it pierces this muscle. In four specimens, there is a communication between MCN and MN was seen. Conclusion: The MCN has significant variations and knowledge of these variations is clinically important in diagnosis and management of peripheral nerve injuries as well as surgical interventions in the arm.